Teacher preparation in the United States : history, current conditions, and policy - Kolodny, Kelly; Breitborde, Mary-Lou (Emerald Publishing Limited, 2022)
Starting in New England with informal training, academies, seminaries, institutes, and the birth of the state normal schools, Kelly Kolodny and Mary-Lou Breitborde explore the origins of teacher preparation in the United States as these models expanded geographically, in substance and form, throughout the South and West. The authors chart how specific historical periods have influenced teacher preparation in the U.S., including Western expansion, industrialization, the Civil War, Reconstruction and retrenchment, the Progressive Era and the mid-to-late twentieth century, which was marked by the space race, the growth of STEM education, racial unrest, the peace movement, immigration and tensions around social inequities. The discussion of teacher preparation in history links contextual issues and themes in each period (e.g., race, the place of women in society, the nation's place in the world) to purposes, policies and practices in the formal preparation of teachers. The authors discuss contemporary issues shaping teacher preparation in the United States and propose recommendations for policy changes. Among their recommendations are the need to diversify the teacher workforce, the commitment to develop strong connections with families and communities, curricula that emphasize teaching for deep understanding, antiracist teacher education and culturally sustaining pedagogy, increased attention to social-emotional learning, the innovative use of new technologies, and the preparation of teachers with a global consciousness.
Includes index.
Keywords: Teachers -- Training of -- United States.; Education -- United States -- History.; Education, Teacher Training & Certification.; Teaching skills & techniques.; elektronické knihy; electronic books